2008
DOI: 10.2320/matertrans.mc200715
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Corrosion Resistance of Anodized Mg-9 mass%Li-1 mass%Zn Alloy

Abstract: This research used pulse and direct current methods to perform surface anodizing treatment of Mg-9 mass%Li-1 mass%Zn alloy (LZ91). The anodic films were analyzed with electrochemical impedance spectroscopy (EIS) for corrosion resistance. The impedance measurements show that the resistance value of anodic films made by pulse current to be 100 K at 2 Â 10 À2 A/m 2 and those made by direct current anodic films to be 65 K at 2 Â 10 À2 A/m 2 . It reveals that pulse current makes better anodic films than direct curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Magnesium silicates and brucite are known to reduce the magnesium corrosion [3,[7][8][9]. Nevertheless, such phases can present various and complex porous form.…”
Section: Processes Occurring During Mgzr Corrosion In Poral Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium silicates and brucite are known to reduce the magnesium corrosion [3,[7][8][9]. Nevertheless, such phases can present various and complex porous form.…”
Section: Processes Occurring During Mgzr Corrosion In Poral Solutionsmentioning
confidence: 99%
“…As the pH of the poral solution coming from geopolymers is around 12, this passive film may be formed, which would explain the decrease of the corrosion rate of Magnesium alloys embedded [5,6]. Second, the presence of dissolved silica within the poral solution is also an asset since it was demonstrated that formation of magnesium silicates by an anodization process on the surface of magnesium improve its resistance regarding its corrosion [7][8][9]. In addition, some authors have shown that silicate sol-gel coating on Mg substrate induces reduction on corrosion [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the corrosion of Mg-Li alloy is more serious than other Mg alloys because Li is very chemically active. The poor corrosion behavior has been a main factor preventing their further applications [1][2][3][4][5][6][7]. However, so far the understanding of the corrosion resistance of Mg-Li alloy is still not very clear.…”
Section: Introductionmentioning
confidence: 99%